2017
DOI: 10.2217/nnm-2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Protects Against Oxidative Stress Induced By SiO 2 Nanoparticles

Abstract: Our findings suggested that Nrf2 could protect against oxidative stress induced by SiO NPs, and the Nrf2/ARE pathway might be involved in mild-to-moderate SiO NP-induced oxidative stress that was evident from dampened activity of Nrf2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…In aging, Nrf2 downregulation was shown to be closely associated with an impaired angiogenesis ability and a progressive reduction in microvascular density, as well as failure in preserving the functional integrity of ECs (Valcarcel‐Ares et al, 2012). Nrf2 also confers an important cellular resistance to electrophilic and oxidative stress (Akino et al, 2018; W. Liu et al, 2017). Lung tissue injuries induced by cerebral ischemia/reperfusion injury can be ameliorated by self‐repairing the EC barrier functions through the Nrf2/HO‐1 axis coupled with HIF‐1α/vascular endothelial growth factor (VEGF) pathways (Fan et al, 2019).…”
Section: Keap1/nrf2 Signaling In Oxidative Stress and Ec Protectionmentioning
confidence: 99%
“…In aging, Nrf2 downregulation was shown to be closely associated with an impaired angiogenesis ability and a progressive reduction in microvascular density, as well as failure in preserving the functional integrity of ECs (Valcarcel‐Ares et al, 2012). Nrf2 also confers an important cellular resistance to electrophilic and oxidative stress (Akino et al, 2018; W. Liu et al, 2017). Lung tissue injuries induced by cerebral ischemia/reperfusion injury can be ameliorated by self‐repairing the EC barrier functions through the Nrf2/HO‐1 axis coupled with HIF‐1α/vascular endothelial growth factor (VEGF) pathways (Fan et al, 2019).…”
Section: Keap1/nrf2 Signaling In Oxidative Stress and Ec Protectionmentioning
confidence: 99%
“…Tokgun et al 23 demonstrated that among 6, 15, and 30 nm sizes of aSiNPs, 6 nm-sized nanoparticles had strongest cytotoxic effects on A549 cells, and this cytotoxicity came from dead receptor-mediated induction of apoptosis. Liu et al 24 examined the cell viability of A549 cells after exposing to SiO 2 particles at various concentrations (5,10,20,30,40,60,80, and 100 μg/mL). Results of CCK-8 assay showed that exposures of 10-20 nm aSiNPs resulted in significantly decreased viability of A549 cells, while 5 μm SiO 2 particles did not affect the cell viability obviously.…”
Section: Size-dependent Cytotoxicity Of Asinps Size-dependent Cytotoxmentioning
confidence: 99%
“…However, compared to 200 nm and 500 nm aSiNPs, 70 nm aSiNPs diminished the cell viability apparently when the serum was absent. In the study of Vo et al, 70 twelve adherent fish cell lines (RTgill-W1, RTgut-GC, RTL-W1, RTBrain, FHML2-6, FHMT-W1, GFB3C, GFSk-S1, GloFish, ZEB2J, EelBrain, and HEW) derived from six species (rainbow trout, fathead minnow, zebrafish, goldfish, haddock, and American eel) were used to investigate the toxic effects of aSiNPs (16,24, and 44 nm). Toxicity produced by aSiNPs appeared to be size-, time-, temperature-, and dose-dependent as well as tissue-specific.…”
Section: Size-dependent Cytotoxicity Of Asinps On Other Kinds Of Cellmentioning
confidence: 99%
“…Moreover, increased ROS generation, oxidative damage, and lung inflammation in Nrf2 KO mice exposed to MWCNTs suggests that Nrf2 is critical towards suppressing the lung inflammatory response [ 90 ]. Another study, summarized in Table 1 , showed that Nrf2 KO mice exposed to silica nanoparticles via intranasal instillation displayed increased generation of reactive oxygen species (ROS) and decreased total antioxidant capacity compared to wild type mice [ 91 ]. This study also suggested that Nrf2 protects against the oxidative stress induced by silica nanoparticles [ 91 ].…”
Section: Deficiency In Cell Signaling Molecules As Determinants Ofmentioning
confidence: 99%
“…Another study, summarized in Table 1 , showed that Nrf2 KO mice exposed to silica nanoparticles via intranasal instillation displayed increased generation of reactive oxygen species (ROS) and decreased total antioxidant capacity compared to wild type mice [ 91 ]. This study also suggested that Nrf2 protects against the oxidative stress induced by silica nanoparticles [ 91 ]. Therefore, the role of Nrf2 in controlling antioxidant protein expression may be critical to resolve inflammatory responses through suppression of ROS generated by ENMs.…”
Section: Deficiency In Cell Signaling Molecules As Determinants Ofmentioning
confidence: 99%